¿Qué busca el Estado con una política pública? Dinámica de las políticas públicas y los valores entre las instituciones estatales (2017)
The law is often used by Colombia as an interesting tool to develope and frame the matters that interest the State. During the latetest years, the public policy documents, are used by diferent authorities in diferent levels and issues, not only the goverment, in their desition making. This happens because this tool implies the Budget, the politics within the matter, and finally the legal frame necesary to implement and execute the desitions. Thas why is interesting to know what does a State looks for in a public policy.